PENGARUH LIKUIDITAS, STRUKTUR MODAL DAN PERPUTARAN KAS TERHADAP PROFITABILITAS PERUSAHAAN - Novanda Derizkyo Naupal; Hesty Ervianni Zulaecha; Hamdanni, Hamdanni; Dewi Rachmania (Pusat Riset dan Inovasi Nasional, 2023)
Profitability shows the company's ability to earn profits related to sales, total assets and capital with certain measurements. The purpose of this study was to determine the effect of liquidity, capital structure and cash turnover on the profitability of empirical study companies in the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2015 - 2019 period. The research approach used is quantitative research. The research period was carried outfor 5 years, namely the 2015 - 2019 period. The population of this study included all food and beverage sub-sector companies listed on the Indonesia Stock Exchange (BEI) for the 2015 - 2019 period. The sampling technique was using purposive sampling technique. Based on the established criteria, 10 companies have met these criteria. The type ofdata used is secondary data obtained from the official website of the Indonesia Stock Exchange. The analysis method used is panel data regression analysis using Eviews software version 9.0. In this study, profitability is measured using return on assets. The results showed that liquidity as measured by the current ratio had a positive effect on profitability, while the capital structure as measured by the debt to equity ratio had no negative effect on profitability as well as cash turnover had no negative effect on profitability. The simultaneous test results for liquidity, capital structure and cash turnover have ajoint effect on profitability.